(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2025)
The Zambia Primary School Syllabus recommends the Communicative Language Teaching (CLT) approach as the methodology to use when teaching English Language as a second language to primary school learners. This implies that teachers should have adequate understanding of the methodology and how to implement it when teaching English language. The study aimed at establishing teachers’ understanding of the Communicative Language Teaching approach as a teaching methodology. The study was qualitative and collected data using face to face interviews. The participants were 20 teachers from three districts in Central province of Zambia who were purposively sampled. The findings were that while teachers were using the Zambia Primary School syllabus, most of them failed to mention recommended methodology in the syllabus which they were supposed to be using to teach English language. Instead, they mentioned some activities used to teach English using CLT. The findings also showed that most teachers had limited understanding of CLT as they failed to describe and explain what it is. Arising from the findings, the study recommended that teacher training colleges should intensively train teachers on the teaching methodologies, and schools should engage in-service teachers in continuous Professional Development (CPD) meetings on pedagogy to help teachers enhance their pedagogical skills.